Evolutionary analysis of Mycobacterium bovis genotypes across Africa suggests co-evolution with livestock and humans - Inlamea, Osvaldo Frederico (2020)
Mycobacterium bovis is the pathogenic agent responsible for bovine tuberculosis (bTB), a zoonotic disease affecting mostly cattle, but also transmittable to humans and wildlife. Genetic studies on M. bovis allow to detect possible routes of bTB transmission and the identification of genetic reservoirs that may provide an essential framework for public health action. We used a database with 1235 M. bovis genotypes collected from different regions in Africa with 45 new Mozambican samples. Our analyses, based on phylogeographic and population genetics' approaches, allowed to identify two clear trends. First, the genetic diversity of M. bovis is geographically clustered across the continent, with the only incidences of long-distance sharing of genotypes, between South Africa and Algeria, likely due to recent European introductions. Second, there is a broad gradient of diversity from Northern to Southern Africa with a diversity focus on the proximity to the Near East, where M. bovis likely emerged with animal domestication in the last 10,000 years. Diversity indices are higher in Eastern Africa, followed successively by Northern, Central, Southern and Western Africa, roughly correlating with the regional archaeological records of introduction of animal domesticates. Given this scenario M. bovis in Africa was probably established millennia ago following a concomitant spread with cattle, sheep and goat. Such scenario could translate into long-term locally adapted lineages across Africa. This work describes a novel scenario for the spread of M. bovis in Africa using the available genetic data, opening the field to further studies using higher resolution genomic data.